Effect of varietal performance on growth attributes and yields of lentil varieties under red and lateritic soil of West Bengal (Journal of Applied and Natural Science, 2018)
A field experiment was conducted during rabi season of 2013-14 and 2014-15 at Agriculture Farm of Palli Siksha Bhavana (Institute of Agriculture), Visva-Bharati, Sriniketan, West Bengal to find out the varietal performance of different promising entries of lentil on growth attributes and yield. Tendifferent varieties viz. Subrata, Asha, Ranjan, HUL 57, BM 6, BM 7, PL 406, KLS 218, Moitree and PL 6 was studied in a randomized block design (RBD), replicated thrice. Different growth and yield attributes were measured in the experiment to find out the suitable variety of lentil for the red and lateritic soil zone of West Bengal. The lentil variety PL-406 showed maximum growth potentiality among the other varieties just followed by another long duration lentil variety KLS-218. The lentil variety PL406 showed maximum growth potentiality among the other varieties just followed by another long duration variety KLS 218. Highest grain yield was obtained from the variety Ranjan (789 kg ha-1 ) followed by the variety PL 406 (785 kg ha-1 ) and KLS 218 (783 kg ha-1 ) respectively. From the result of the present experiment, it can be concluded that the variety PL 406 gave maximum vegetative growth, whereas the variety Ranjan produce maximum yield and found most potential variety among other lentil varieties under red and lateritic soil of West Bengal